Fruit and vegetable production for export - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
Production of ACP fresh fruits and vegetables for export to the EEC 1993 298pp ISBN 92 9081 0955 published by CTA